Appropriate antibiotic use reduces length of hospital stay. (15th December 2016) - van den Bosch, Caroline M. A.; Hulscher, Marlies E. J. L.; Akkermans, Reinier P.; Wille, Jan; Geerlings, Suzanne E.; Prins, Jan M.
Abstract : Objectives: To define appropriate antibiotic use in hospitalized adults treated for a bacterial infection, we previously developed and validated a set of six generic quality indicators (QIs) covering all steps in the process of antibiotic use. We assessed the association between appropriate antibiotic use, defined by these QIs, and length of hospital stay (LOS). Methods: An observational multicentre study in 22 hospitals in the Netherlands included 1890 adult, non-ICU patients using antibiotics for a suspected bacterial infection. Performance scores were calculated for all QIs separately (appropriate or not), and a sum score described performance on the total set of QIs. We divided the sum scores into two groups: low (0%–49%) versus high (50%–100%). Multilevel analyses, correcting for confounders, were used to correlate QI performance (single and combined) with (log-transformed) LOS and in-hospital mortality. Results: The only single QI associated with shorter LOS was appropriate intravenous–oral switch (geometric means 6.5 versus 11.2 days; P  < 0.001). A high sum score was associated with a shorter LOS in the total group (10.1 versus 11.2 days; P  = 0.002) and in the subgroup of community-acquired infections (9.7 versus 10.9 days; P  =   0.007), but not in the subgroup of hospital-acquired infections. We found no association between performance on QIs and in-hospital mortality or readmission rate. Conclusions: Appropriate antibiotic use, defined by validated process QIs, in hospitalized adult patients with a suspected bacterial infection appears to be associated with a shorter LOS and therefore positively contributes to patient outcome and healthcare costs.